Practicality of E-module based on Discovery Learning on the Reaction Rate material equipped with a Virtual Laboratory for Class XI SMA - Bundani Sakinah Alora; Hardeli Hardeli (Entalpi Pendidikan Kimia, 2022)
The 2013 curriculum is a rules that makes students more active both in learning and in technological development. Teaching materials are called practical if the practitioner has stated that they can be applied in the field. This study aims to reveal the practicality of discovery learning-based e-modules on the reaction rate material equipped with a virtual laboratory for class XI SMA. This type of research is Research and Development (R&D). The research method used is the Plomp development model. The research was conducted at SMAN 14 Padang. Data were analyzed by Aikens’V formula. The results obtained at the one to one evaluation stage show that the e-module uses clear letters, covers and attractive designs., the language used is easy to understand, coherent presentation of material, videos and animations can help students understand the material. The results of the analysis of the practicality value obtained 87%. This data is evidenced by the ability of students to answer e-module questions by 78,9%. Based on the data analysis, it was concluded that the discovery learing based e-module on the reaction rate material equipped with a virtual laboratory was declared practical.